Eating Habits of Football Players Training in Sports Clubs in the Żywiec District - Faruga-Lewicka, Wioleta; Pietraszko, Zuzanna; Staśkiewicz, Wiktoria; Kardas, Marek; Kardas, Justyna (Journal of Education, Health and Sport, 2023)
Background. Football is one of the most popular sports at both amateur and professional levels. The discipline is constantly evolving. At the same time, an increase in physiological demands can be observed. Players are exposed to significant energy expenditure. Therefore, it is necessary to ensure an adequate level of nutrition. The purpose of this study was to evaluate the diet and eating habits of football players training in sports clubs in the Żywiec district. Methods. The survey was conducted among football players who were players of football clubs in the Żywiec district. Only men were considered, and the study group consisted of 205 athletes. A questionnaire, which was made available as an electronic form, was used to obtain the results. The questionnaire used questions from the KomPAN questionnaire and the author's questions, which accounted for the bulk of the 35 questions. Results. The dietary quality of football players from the Żywiec district was found to be low. This is noticeable in the diet used on a daily basis, as well as considering nutrition around training or matches. Conclusions. Poor nutrition quality involves many aspects that require attention. This applies to both the frequency of consumption of certain foods and the eating habits practiced. Attention should be paid to improving match-day and training-day nutrition. Nutrition education in clubs should be emphasized.